Evaluation of parabolic antenna types and their application in TVRO systems - Ibrahim, Raed A. R.; Al-Khateeb, Khalid A. Saeed; Islam, Md. Rafiqul (2005)
Considerations relating to the parabolic dish reflector antennas are discussed. The characteristics, efficiency and construction for a variety of dish antennas are analyzed. Actual measurements and tests were made and a comparative study of the performance of screen mesh and solid antennas is presented. TVRO signal reception levels from a number of geo stationary satellites were used as criteria for the assessment.